Investigating Impact of ChatGPT on Creativity Among Literature and Non-English Majors in Bangladeshi Private Universities - Tasleem Ara Ashraf (Naifaderu Cipta Sejahtera, 2025)
Purpose The rapid rise of artificial intelligence tools, particularly ChatGPT, has transformed academic learning and creativity among university students. This study explores the comparative impact of ChatGPT usage on creativity among literature students and non-English majors. Specifically, it examines how students use ChatGPT, the challenges they face, and the effects of AI reliance on creative thinking and problem-solving. Methodology A mixed-methods approach was adopted, utilizing a structured questionnaire to collect data from both groups. The quantitative component, through a structured survey, will measure usage patterns, perceived benefits, challenges, and the perceived impact on creativity. The qualitative component, using open-ended survey responses, will capture deeper insights into students’ experiences, helping to explain the patterns observed in the quantitative data. This approach allows for triangulation, enhancing the validity and reliability of the study’s findings Results/Findings Findings suggest that while literature students tend to use ChatGPT as a tool to enhance idea generation and critical thinking, non-English majors are more likely to depend on it for ready-made answers, potentially limiting their creative engagement. Common challenges identified include inaccurate outputs, difficulty in formulating effective prompts, and occasional over-reliance on AI assistance. The study proposes a “Differential AI-Mediated Creativity” framework, highlighting that the impact of AI on creativity is mediated by students’ academic background, motivation, and engagement. Implication These insights emphasize the need for guided AI integration in academic settings, enabling students to harness ChatGPT effectively without compromising independent thinking. The research contributes to understanding how AI tools can be leveraged to foster creativity while minimizing dependency across diverse academic disciplines